Management of Islamic Religious Sciences Curriculum Based On The Yellow Bible and Respected In Islamic at The Muada Islamic Islamic Boarding School - Achmad Muharam Basyari; Heru Sujiarto; R. Supyan Sauri; Helmawati Helmawati (Journal of Social Science, 2021)
The education curriculum occupies a strategic position. The Islamic religious science curriculum is the basis for achieving the goals that have been stated in the document and implemented in the process to realize competent students. Proper curriculum management is needed based on the yellow book and is considered Islamic. On that basis, this study aims to find: (1) planning Islamic religious science curriculum; (2) organization of Islamic religious science curriculum; (3) implementation of Islamic religious science curriculum; (4) evaluation of Islamic religious science curriculum; (5) obstacles in implementing the Islamic religious science curriculum; (6) solutions in implementing the Islamic religious science curriculum. This research uses a qualitative approach with the type of case study. Technical data collection through in-depth interviews, observation, and documentation. Data analysis through data collection, data reduction, data presentation, concluding, and verification stages. This study resulted that: (1) curriculum planning at both Islamic boarding schools was carried out by determining curriculum objectives and contents, determining Human Resources (HR), preparing educational programs, compiling academic calendars and schedule activities; (2) organization is carried out by determining the pattern of curriculum organization, placement of Human Resources (HR); 3) implementation is carried out by means of socialization and direction, preparing lesson plans, determining approaches, strategies, and learning methods, providing learning resources and media, and structuring classes; 4) curriculum evaluation is carried out by carrying out learning evaluations, literacy competency evaluations, and communication; 5) obstacles in implementing the curriculum can be seen from psychological factors, sociological factors, and technical factors; 6) solutions and future improvement efforts in implementing the curriculum can be seen from psychological factors, sociological factors, and technical factors.